A Inquisição Portuguesa e seus reflexos no Brasil colonial no século XVI - Cornélio, Priscilla Guimarães (2017)
The relevance of the theme stems from the fact that the Portuguese Inquisition brought a new structure, with different forms of power and organization, such as customary law, by written codes, allowing a centralization of power, as well as building a persecutory society in Portugal, And in Brazil, stressing that they have remnants of this system until the present day. It is necessary to critically reflect on the events that occurred during this period, in order to make them relevant within the school environment, giving students more information regarding the country in which they live and what happened during the inquisitorial period. It is worth mentioning that the central focus is on the precariousness of the subject during class, and the Inquisition is considered an important time for the modification of the political, historical and legal system of Brazilian society, being the main responsible for countless Changes in relation to penalties, motivations, creation and maintenance of political and religious powers, among others. It is emphasized that the research aims, finally, the creation of diverse tools, regarding the creation of the object of learning, so that they can help and lead to the students of the high school the understanding of the researched historical content, given the impossibility, Even if only temporary, to deepen this theme within the classroom.